Traveller and fan identities of the Finnish football fans - Tikander, Juha (2010)
This research deals with the Finnish football fans and their motives to travel and follow sports. The reason for studying this area is to increase information and knowledge about the consumer behaviour of sport fans. Special attention is paid to the question of why fans behave the way they do. What factors affect fans’ decision making processes when they travel? Does sport have an influence on the travelling process? Are there any similarities between the reasons of travelling and attending sport events? In this study sport fans are divided into different fan types according to their motives to attend sport events as spectators and in different traveller typologies according their motives to travel abroad. The research was conducted as an online survey. The survey was posted to the active Finnish online football discussion forums, Futisforum and Futisforum2 and e-mail posted to the ELK (Finnish association of English league supporters) and SMJK (Official supporters club of Finnish national football team). The results were analysed using the quantitative methods, such as factor analysis and cross tabulation. The results of the research show that football fans are rather active travellers. For many fans attending a sport event is a reason to travel abroad. In addition, merely the possibility to attend a sport event had a definite influence in planning a trip abroad. The results also reveal that for the most Finnish football fans attending a sport event is a social activity. In fact it seems that the whole idea of being a fan is heavily based on its social nature. For most fans travelling seemed to be a good way of spending time with the family and friends. The reasons for travelling and attending sport events were strikingly similar. Besides gaining social experiences the main reasons for participating in sport events were entertainment value and new experiences. Based on this study it can be concluded that sport has an influence on fans’ decision making process when the decisions of the travel destination are being made. The study also indicates that reasons to travel and reasons to attend sport events are very similar to the fans. However, Finnish football fans can not be seen as a homogeneous group as they have multiple traveller and fan identities. The clear majority of the fans is, however motivated about new experiences, socialising and entertainment when travelling or attending sport events as spectators.